2022
DOI: 10.2147/rrtm.s351268
|View full text |Cite
|
Sign up to set email alerts
|

Liver Enzymes and Lipid Profile of Malaria Patients Before and After Antimalarial Drug Treatment at Dembia Primary Hospital and Teda Health Center, Northwest, Ethiopia

Abstract: Background: Infection with malaria in humans involves liver cell destruction, which alters the levels of liver enzymes and lipid profiles. A number of studies have been conducted to address the impact of malaria on liver enzymes and lipid profiles but no studies were addressed after antimalarial treatment in Ethiopia. This study is intended to fill this gap. Methods: An observational cohort study was conducted at Dembia Primary Hospital and Teda Health Center, from June to August 2020. Eighty eight malaria inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
7
2
Order By: Relevance
“…In contrast to an increase in the liver enzyme that was observed in previous studies, we observed no elevation of liver enzyme in this study ( Viriyavejakul et al., 2014 ; Rocha et al., 2015 ; Dinkar et al., 2020 ; Megabiaw et al., 2022 ); however, abnormalities in the ratio of aspartate aminotransferase to alanine aminotransferase were observed in 43% of the patients, and higher ratios of aspartate aminotransferase to alanine aminotransferase were significantly associated with malaria parasitemia. The liver enzyme profiles are distinct from prior studies ( Viriyavejakul et al., 2014 ; Dinkar et al., 2020 ; Megabiaw et al., 2022 ). Based on the findings on the clinical history of prior prophylactic administration, we speculate that adherence to prophylactic treatment with antimalarial medications before and after infection has a hepatoprotective role.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to an increase in the liver enzyme that was observed in previous studies, we observed no elevation of liver enzyme in this study ( Viriyavejakul et al., 2014 ; Rocha et al., 2015 ; Dinkar et al., 2020 ; Megabiaw et al., 2022 ); however, abnormalities in the ratio of aspartate aminotransferase to alanine aminotransferase were observed in 43% of the patients, and higher ratios of aspartate aminotransferase to alanine aminotransferase were significantly associated with malaria parasitemia. The liver enzyme profiles are distinct from prior studies ( Viriyavejakul et al., 2014 ; Dinkar et al., 2020 ; Megabiaw et al., 2022 ). Based on the findings on the clinical history of prior prophylactic administration, we speculate that adherence to prophylactic treatment with antimalarial medications before and after infection has a hepatoprotective role.…”
Section: Discussioncontrasting
confidence: 99%
“…Many of these molecules promote vasculature occlusion for inducing inflammation and endothelial cell activation and induce acute-phase responses to prevent the spread of malaria. Routine laboratory results indicate liver and kidney dysfunction ( Nieman et al., 2009 ; Nantakomol et al., 2011 ; Mita-Mendoza et al., 2013 ; Mangal et al., 2017 ; Cheaveau et al., 2019; Dinkar et al., 2020 ; Khrapunov et al., 2021 ; Tona Lutete et al., 2021 ; Megabiaw et al., 2022 ), and in some cases, abnormal myocardial enzyme is reported ( Herr et al., 2011 ; Dinkar et al., 2020 ; Kaiser et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The levels of LDL and HDL were observed in these patients, the average was 56.6 and 56.2, respectively. A study from India [16] reported triglyceride result was higher than the normal reference range in malaria, which was in disagreement with our results, while we found similar results of cholesterol and LDL levels of the study participants were within the normal reference range. Several studies have reported a significant association between LPL gene polymorphisms and lipids profile [17].…”
Section: Discussioncontrasting
confidence: 99%
“…This can be explained by the invasion of hepatic cells by the parasite and the leakage of liver enzymes into the circulation. The increase in liver enzyme levels is also proportional to the severity of the malaria infection ( Megabiaw et al, 2022 ; Ahad et al, 2022 ). Liver dysfunction in malaria cases results from congestion, cellular inflammation, and sinusoidal blockage caused by the parasite ( Auta, Zakariyya & Everest, 2018 ).…”
Section: Resultsmentioning
confidence: 99%